Vibration based damage assessment of type 1 compressed natural gas cylinder - Zhang, Yao (2015)
Compressed Natural Gas (CNG) is widely used around the world due to its environmentally friendly nature and significantly less cost as compared to other conventional fuels such as petrol, diesel and Liquefied Petroleum Gas (LPG). A typical 30 L or 40 L CNG cylinder fitted in vehicle usually experiences a larger number of pressurization cycles during its service life than other cylinders used in the industry. When these CNG cylinders are approaching their service lifespan, defects such as corrosion and surface cracks are discovered. If the defects increase to certain sizes, the allowable internal pressure of the damaged CNG cylinder will be lower than the service internal pressure, making them extremely unsafe. In fact, there have been several serious CNG cylinder explosion accidents in the past decades. Therefore, it is crucial to carry out periodic inspections and testing to prevent such catastrophic failure. A few methods have been used for many years but they are still somehow unreliable, time consuming and expensive. The ultimate aim of this research is to propose and develop a quick, convenient and reliable technique to determine the category, location and severity of damages occurring in Type 1 all metal CNG cylinders. The typical damage is corrosion occurring on the internal surface, whereby reducing wall thickness; it is distinguished into global corrosion covering a large area and local corrosion having strip like shape. Although crack seldom occurs in practice, once it is present, it is dangerous as it may cause catastrophic rupture. Therefore, inspecting and assessing the damage of crack at the early stage has to be carried out as well. Firstly, the relationship between natural frequencies and wall thickness reduction is derived and analyzed from which the corrosion can be distinguished whether it is global corrosion or local corrosion. For global corrosion, wall thickness reduction covers a large area and the severity can be evaluated accordingly. Because the weight of accelerometer sometimes cannot be ignored, it is considered as an auxiliary mass; the influence of auxiliary mass on the frequencies of CNG cylinders is studied and a method to eliminate such influence is proposed and validated by both numerical examples and experimental tests. Secondly, a new concept called Frequency Shift Curve (FSC) is proposed, which represents the change of frequency with respect to the position of the auxiliary mass attached on the cylinder. The FSC is related to the square of mode shapes, and therefore, the circumferential FSCs have periodic peaks and troughs; in particular, the fundamental circumferential FSC which can be measured more easily and accurately is sensitive to local corrosion, and the trough with minimum value indicates the circumferential location of local corrosion. Then, the curvature of fundamental longitudinal FSC is utilized for locating the longitudinal location. Finally, the idea of FSC is extended to Frequency Shift Surface (FSS) and a novel damage index based on FSS and the similarity of longitudinal FSCs is proposed. For both a single and multiple local corrosions, not only the locations can be determined, the sizes and severities can also be assessed by this damage index. In addition, it does not require prior information from undamaged CNG cylinders which is difficult to obtain in practice. The damage due to crack in a 7 L CNG cylinder is also investigated in details, and it shows good performance in both numerical examples and experimental results.